Cognitive function and its associations in older adults from Amazonas, Brazil - Freitas, Duarte Luís (2019)
The objectives of this study were: (1) to investigate the age-related differences in cognitive function (CF), nutritional status (MNA), physical activity (AF), quality of life (QoL), depression, social satisfaction (SS) and socioeconomic status (SES), and (2) to explore the relationships between CF and the previous variables. This cross sectional study included 268 men and 433 women (aged 71.4 ± 7.0 years). CF was determined with the Cognitive Telephone Screening Instrument (COGTEL) and the Mini-Mental State Examination (MMSE). Correlates were as follows: Mini Nutritional Assessment (MNA), PA (Baecke questionnaire modified for older adults), Quality of life (QoL SF12), Geriatrics Depression Scale (GDS), Satisfaction and Social Support Scale, and Socioeconomic status (SES). All instruments were applied in a face to face interview. An independent t-test identified significantly higher scores in young-old adults (≤ 69 years) for CF (p < 0.001), PA (p = 0.046) and SES (p = 0.007), compared to old-old adults (≥ 70 years). The results of multiple linear regression analysis indicated that the most significant CF correlates were SES (β = 0.45; p < 0.001), age (β = -0.12; p < 0.001), SS (β = 0.12; p = 0.001), GDS (β = -0.11; p = 0.003) and QoL (β = 0.08; p = 0.017). The overall regression model explained 36% of the total variance in the COGTEL. The oldest and the more depressed adults obtained lower scores for FC. The present study suggests that, between the correlates studied, SES was the strongest predictor in the explanation of CF in older adults.